Cultivation of horticultural crops pays - Swarnam, T P; Velmurugan, A; Jaisankar, I; Wamen, Ajit; Panwar, A S (Indian Horticulture, 2019)
With increasing population and the need to ensure livelihood security, it is imperative to evolve a suitable strategy for augmenting production through onfarm and off-farm activities. By integrating horticulture crops and other agricultural activities based on the resource endowment and constraints of different locations, it is possible to improve the farm production as well as employment opportunities of the individual farm households in the island. Compared to a monocropped situation, intercropping with spices, tubers and vegetables with the existing coconut and arecanut plantations enhances employment opportunities and diversified farm produces. Land shaping and rainwater harvesting in the coastal lowlands opens up wide opportunity for intensive vegetable cultivation in these areas. Such system presents a higher degree of resource use efficiency, productivity, sustainability and nutritional security. This will reduce the external dependence of islands for livelihood.